Compact microwave hairpin line band pass filter using folded quarter-wave resonator - Dahlan, Samsul Haimi (2005)
Compact mIcrowave hairpin band pass filter using half-wavelength folded resonator as a method to miniaturize resonator structure has been thoroughly studied in this thesis. Design were done by using the mathematic formulas and verified by using SONNET LITEPlus 8.0 software. Synthesis of the filter is using the insertion loss method. The initial design of a miniature hairpin filter was achieved by carefully selecting the resonator shape and the initial frequency. The shape was then fine tuned, and the response for the changes was plotted. This would indirectly represent the behavior of the circuit when parameter variation occurs. The step by step procedure to design the filter is presented. The design performance and characteristics in terms of electrical and physical parameters were compared with the conventional hairpin filter. The final design of the miniaturized hairpin filter has an overall size of 46% smaller compared to the conventional hairpin size. Better return loss properties were also observed from the miniaturized version. The first spurious frequency occurs at a higher frequency compared to that of the conventional hairpin filter. It is tunable depending on the value of the even-mode impedance that was chosen at the early stage of the design process. The bandwidth, however, was slightly narrower, which is 80% of the desired 1 00 MHz. In terms of the response, miniaturized hairpin filter is having steeper skirting. However, it is comparable to that of the conventional hairpin filter.